2020
DOI: 10.20885/jsb.vol24.iss2.art8
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Muslim non-consumers’ intention to use Islamic bank: perceived social value (PSV) and awareness

Abstract: As a country with the largest Muslim population in the world, Indonesia has a greater market opportunity for Islamic bank than the conventional. When it compares with other Islamic countries, the market share of Islamic banks is still less appealing. This situation is certainly an interesting problem to be researched. The purpose of this study is to examine the influence of subjective norms, awareness, perceived values, attitudes, and intentions to use Islamic banks based on the Theory of Planned Behavior. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
0
0
Order By: Relevance
“…The results also demonstrated that the behavioral intention to use digital public services is directly and favorably impacted by perceived awareness, which supported Hypothesis H2 and is consistent with earlier research (e.g., Abdurakhimovna et al 2021;Alzoubi et al 2019;Hasan et al 2018;Mason and Nassivera 2013;Pantari and Aji 2020;Yuan and Jang 2008). This means that most users of electronic public service websites in Saudi Arabia are familiar with these websites and know the benefits of using them.…”
Section: Discussionsupporting
confidence: 89%
“…The results also demonstrated that the behavioral intention to use digital public services is directly and favorably impacted by perceived awareness, which supported Hypothesis H2 and is consistent with earlier research (e.g., Abdurakhimovna et al 2021;Alzoubi et al 2019;Hasan et al 2018;Mason and Nassivera 2013;Pantari and Aji 2020;Yuan and Jang 2008). This means that most users of electronic public service websites in Saudi Arabia are familiar with these websites and know the benefits of using them.…”
Section: Discussionsupporting
confidence: 89%
“…Therefore, TPB cannot stand alone for this research, yet the implementation of TPB as a grand theory to explore the features that influence the intention of young SME leaders to embrace the incorporation of Islamic microfinance is deemed appropriate. The novel constructs are the perceived financial benefits as suggested by Aigbovo & Idolor (2022) and Kristanto (2022) and perceived financial cost (Amini et al, 2020;Fauzi et al, 2020), in conjunction with awareness (Aviva & Kusuma, 2021;Pantari & Aji, 2020), religiosity, and knowledge (Maryam et al, 2019) underpinning the TPB towards attitude to construct the aid to amplify the predictive efficacy. H1: Intention to adopt Islamic microfinance has a positive effect on the adoption of Islamic microfinance.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Also, the preference for extending the TPB is rooted in its capacity to accommodate the idiosyncrasies of Islamic financial contexts. Thus, this study merges the TPB posited by Ajzen (1991), wherein he emphasized that human conduct manifests through potent inclinations or volition, with new variables, including the perception of financial benefits (Aigbovo & Idolor, 2022;Kristanto HC, 2022) and perceived financial cost (Amini et al, 2020;Fauzi et al, 2020) along with awareness (Aviva & Kusuma, 2021;Pantari & Aji, 2020), religiosity, and knowledge (Maryam et al, 2019) behind TPB towards attitude in order to construct the aid to amplify the predictive efficacy. Taking into consideration these factors, the outcomes acquired are expected to offer practicality to Islamic financial institutions in the endeavor to formulate more effective marketing strategies for Islamic microfinance offerings.…”
mentioning
confidence: 98%
“…Meanwhile, in 2060 it is estimated that Indonesia will have 253 million Muslim population or 8.5% of the world's population. Because in 2060 the largest Muslim population will be led by India, which is 333 million Muslims or 11.1% of the total Muslim population in the world (Pantari & Aji, 2020).…”
Section: Introductionmentioning
confidence: 99%